Formation mechanism of the upper Paleozoic tight sandstone gas reservoir in the Daniudi gas field, Ordos Basin, China - Song, Fan; Kong, Qingyuan; Su, Nina; Jiao, Guohua; Xu, Miaomiao (Frontiers in Earth Science, 2024)
The upper Paleozoic gas reservoir in the Daniudi gas field, Ordos Basin, is one of the typical tight sandstone gas reservoirs in China. Research into the sequential order of reservoir densification and gas accumulation is the key to revealing the formation mechanism of tight sandstone gas reservoirs.However, this scientific issue is still a subject of debate in the Daniudi gas field. Based on a series of reservoir experiments and in combination with stratigraphic burial and thermal maturity history, a comprehensive study is conducted on the formation and natural gas accumulation processes of the upper Paleozoic sandstone reservoir in the Daniudi gas field. Study results indicate that the main causes of sandstone reservoir densification of the study area include long-term compaction, multistage quartz cementation and carbonate cementation. In accordance with the time order of reservoir densification and gas accumulation, the formation of tight gas reservoirs can be divided into two types: self-sourced and near-source accumulations. In the former, before sandstone reservoir densification occurs, low-maturity natural gas generated from coal rocks and dark mudstones enter the reservoir quickly, migrate towards structural highs as driven by buoyancy, and then accumulate and form gas reservoir in favourable lithologic traps. In the latter, after tight sandstone reservoirs are formed, high-maturity gas migrates along fractures formed in the Late Cretaceous and accumulate in the nearby reservoir with micro-fractures. The study results provide a new understanding of the formation process of tight sandstone gas reservoirs and provides a reference for the exploration and development of the same type gas reservoirs.